Prevalence and predictors of medication non-adherence in children with inflammatory bowel disease in China: A cross-sectional study - Wu, Yuanyuan; Huang, Lingfei; Sun, Jin; Wang, Huijuan; Fang, Luo; Miao, Jing (Frontiers in Pharmacology, 2022)
Background: Non-adherence to physician-prescribed medications, especially oral medications, is common in children with inflammatory bowel disease (IBD), and medication non-adherence is associated with poorer outcomes in IBD. Therefore, understanding and improving medication adherence in children with IBD is critical. Objective The aim of this study was to investigate the prevalence of medication non-adherence and its risk factors in children with IBD in China to provide a basis for developing adherence improvement strategies. Methods A cross-sectional design was employed. Children (aged <18 years) with IBD who visited the Children's Hospital, Zhejiang University School of Medicine, from September 2020 to December 2021 were included. Data were collected by questionnaires. Subsequently, forward stepwise binary logistic regression analysis was performed to determine independent predictors of medication non-adherence. Results A total of 119children were included. The results showed that 33 (27.73%) and 86 (72.27%) children had poor and good medication adherence, respectively. Of these, 83 (69.75%) had forgotten to take their medications sometimes, often, or always. On binary logistic regression, we found that the incidence of medication non-adherence in children with IBD course of 3 years and above [OR 4.82 (95%CI: 1.47-15.88); P = 0.01] was significantly higher than that in children with course of 3 months to 1 year, whereas children with higher parental CCKNOW scores [OR 0.77 (95%CI: 0.67-0.88); P = 0.00] had significantly lower incidence of medication non-adherence than those with lower parental CCKNOW scores, and the results of the correlation between parental knowledge scores of the four categories and children's medication adherence showed that drug knowledge scores (r = 0.36, p < 0.00) and complication knowledge scores (r = 0.24, p = 0.01) were positively correlated with medication adherence. Conclusions: Poor medication adherence in children with IBD in China was common, and forgetting to take medication was the main barrier. Longer disease duration (3 years and above) in children could act as a risk factor for medication adherence, whereas higher level of parental knowledge about IBD could act as a protective factor. Our results may inform on the design and implementation of medication adherence interventions for children with IBD.